Penggunaan Second Account Instagram Sebagai Self Disclosure Di Kalangan Mahasiswa UINSU - Hasibuan, Wilda Lestari; Azhar, Anang Anas (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This study aims to determine the use of Instagram second account as self-disclosure among UINSU students. This research uses a descriptive qualitative approach that is sourced from interviews, observation, and documentation then uses self-disclosure theory or Johari window. Determination of informants using purposive sampling technique is as many as 6 informants. The results of this study indicate that the forms of self-disclosure of UINSU students are a) open, b) dark, c) hidden, and d) unknown. The reason for self disclosure on second account instagram is to express themselves, share daily life, college assignments and just want to find information that is personal.